Missed opportunities for chronic diseases prevention in a primary health care center in Istanbul [Istanbul'da bir birinci basamak saǧlık kuruluşunda kronik hastalıklardan korunmada kaçırılmış fırsatlar] - TOPUZOĞLU, AHMET; HIDIROĞLU, SEYHAN (Gulhane Military Medical Academy, 2011)
AIM: The aim of the study was to investigate missed opportunities about chronic diseases and related risk factors in a primary health care center in Istanbul. METHOD: This descriptive study was held in a Primary Health Care Center in Istanbul with the study population consisted of 500 people which were applicated in one month period. Participants were asked; if they were questioned by their physician about major risk factors (smoking, obesity, diabetes mellitus, hypertension, coroner heart disease in family, glysemic level, cholesterol level) and regular exercise practice according to Primary Care 2006 Guidelines. The data was evaluated by descriptive statatistics, chi square test. RESULTS: The median age of the participants were 40 (25.p; 32-75.p;52) and 76.4% of them were female. 50.4% of participants were overweight, 20.8% of them were obese. 36.2% of them were smoking, 22.0% were hypertensive, 10.4% were hiperglysemic. There were around 90.0% missing opportunities screening and management of obesity and blood cholesterol level, 70.0% about hypertension and 85.0% about diabetes. CONCLUSION: Opportunities about chronic diseases and their risk factors are being missed and asking about risk factors are neglected in primary health care center.
Keywords: Chronic disease; Missed opportunity; Prevention; Risk factor